Use of Adjuncts to Supplement Judicial Resources in Six Jurisdictions, 1983-1986: (United States) - Aikman, Alexander ([Verlag nicht ermittelbar], 1989)
This multi-site data collection evaluates the impact of judicial adjunct attorneys and referees on the court system at the county and state levels in six jurisdictions: (1) Pima County, Arizona, (2) Multnomah County, Oregon, (3) King County, Washington, (4) Hennepin County, Minnesota, (5) Phoenix, Arizona, and (6) the state of Connecticut. There are three different units of observation in this study: (1) civil trial cases, (2) trial judges, including regular judges and adjunct attorneys, and (3) litigating attorneys. The court case data include information on type of case, date of trial, type of judge, type of disposition, and date of disposition. For the questionnaire data obtained on judges, adjuncts, and litigating attorneys, information includes experience with the program, satisfaction, and ideas for changes.